The antiestrogen ICI 182,780 decreases the expression of estrogen receptor-alpha but has no effect on estrogen receptor-beta and androgen receptor in rat efferent ductules - Prins Gail S; Franca Luiz R; Carnes Kay; Nie Rong; Oliveira Cleida A; Saunders Philippa TK; Hess Rex A (BMC, 2003)
Abstract Background The antiestrogen ICI 182,780 has been used successfully as an alternative experimental model for the study of estrogen action in the rodent adult male reproductive tract. Although ICI 182,780 causes severe alterations in testicular and efferent ductule morphology and function, the effects on the expression of estrogen and androgen receptors in the male have not been shown. Methods In the present study, adult male rats were treated with ICI 182,780 for 7 to 150 days, to evaluate the time-response effects of the treatment on the pattern of ERα, ERβ and AR protein expression in the efferent ductules. The receptors were localized using immunohistochemistry. Results ERα, ERβ and AR have distinct cellular distribution in the testis and efferent ductules. Staining for ERα is nearly opposite of that for ERβ, as ERα shows an increase in staining intensity from proximal to distal efferent ductules, whereas ERβ shows the reverse. Androgen receptor follows that of ERα. ICI 182,780 caused a gradual but dramatic decrease in ERα expression in the testis and efferent ductules, but no change in ERβ and AR expression. Conclusions The differential response of ERα and ERβ proteins to ICI 182,780 indicates that these receptors are regulated by different mechanisms in the male reproductive tract.